Reliability and Validity of the Red Flag App: Encouraging Inclusive Education for Children at Risk in the School System - Franzina Coutinho; Sonali Saini (International Journal of Education, 2024)
Early identification of ‘risk for disability and mental illness’ has many advantages including better prognosis, and an improved quality of life. Teachers and school management spend long contact hours with children, and are typically among the first to notice developmental delays or behavioural changes. Although they are uniquely poised to identify risks, this often does not occur due to lack of teacher training. In India, there is a dearth of trained therapists for children with special needs. Additionally, many teachers have not been adequately trained in identifying and helping children with mental health issues, neurodevelopmental disabilities, or learning disabilities. The current study seeks to validate an online app which can aid teachers in identifying children at risk across seven areas namely Attention Deficit Hyperactivity Disorder (ADHD), Autism Spectrum Disorder issues (ASD), abuse issues, intellectual deficits, mental health issues, specific learning disorders (SLD), and visual deficits. These buckets have been identified through expert focus group discussions and appropriate literature reviews. The current paper describes the necessity and relevance of such an instrument, and outlines the validation process being conducted.